Thiomicrorhabdus streamers and sulfur cycling in perennial hypersaline cold springs in the Canadian high Arctic. (20th January 2020) - Magnuson, Elisse; Mykytczuk, Nadia C.S.; Pellerin, Andre; Goordial, Jacqueline; Twine, Susan M.; Wing, Boswell; Foote, Simon J.; Fulton, Kelly; Whyte, Lyle G.
Summary: The Gypsum Hill (GH) springs on Axel Heiberg Island in the Canadian high Arctic are host to chemolithoautotrophic, sulfur‐oxidizing streamers that flourish in the high Arctic winter in water temperatures from −1.3 to 7°C with ~8% salinity in a high Arctic winter environment with air temperatures commonly less than −40°C and an average annual air temperature of −15°C. Metagenome sequencing and binning of streamer samples produced a 96% complete Thiomicrorhabdus sp. metagenome‐assembled genome representing a possible new species or subspecies. This is the most cold‐ and salt‐extreme source environment for a Thiomicrorhabdus genome yet described. Metaproteomic and metatranscriptomic analysis attributed nearly all gene expression in the streamers to the Thiomicrorhabdus sp. and suggested that it is active in CO2 fixation and oxidation of sulfide to elemental sulfur. In situ geochemical and isotopic analyses of the fractionation of multiple sulfur isotopes determined the biogeochemical transformation of sulfur from its source in Carboniferous evaporites to biotic processes occurring in the sediment and streamers. These complementary molecular tools provided a functional link between the geochemical substrates and the collective traits and activity that define the microbial community's interactions within a unique polar saline habitat where Thiomicrorhabdus ‐dominated streamers form and flourish.